Drought stress modulates cuticular wax composition of the grape berry. (27th January 2020) - Dimopoulos, Nicolas; Tindjau, Ricco; Wong, Darren C J; Matzat, Till; Haslam, Tegan; Song, Changzheng; Gambetta, Gregory A; Kunst, Ljerka; Castellarin, Simone D
Abstract: Drought events are a major challenge for many horticultural crops, including grapes, which are often cultivated in dry and warm climates. It is not understood how the cuticle contributes to the grape berry response to water deficit (WD); furthermore, the cuticular waxes and the related biosynthetic pathways are poorly characterized in this fruit. In this study, we identified candidate wax-related genes from the grapevine genome by phylogenetic and transcriptomic analyses. Developmental and stress response expression patterns of these candidates were characterized across pre-existing RNA sequencing data sets and confirmed a high responsiveness of the pathway to environmental stresses. We then characterized the developmental and WD-induced changes in berry cuticular wax composition, and quantified differences in berry transpiration. Cuticular aliphatic wax content was modulated during development and an increase was observed under WD, with wax esters being strongly up-regulated. These compositional changes were related to up-regulated candidate genes of the aliphatic wax biosynthetic pathway, including CER10, CER2, CER3, CER1, CER4, and WSD1 . The effect of WD on berry transpiration was not significant. This study indicates that changes in cuticular wax amount and composition are part of the metabolic response of the grape berry to WD, but these changes do not reduce berry transpiration. Abstract : Water deficit caused an increase in grape berry aliphatic cuticular wax load and changes in wax composition, yet these modifications did not reduce the berry cuticle transpiration rate.